Knowledge, views and practices of males in natural family planning: an evaluation of husband education session (HES) in Moncada, Tarlac in 1998. - Mellejor, Mersole C. (Animo Repository, 1999)
This study evaluates the Husband Education Session (HES) that was conducted in Moncada, Tarlac in 1998 to train males in Natural Family Planning (NFP).This study employed a quasi-experimental (post test only non-equivalent control group) design. The respondents of the study were two HES facilitators, 25 HES participants (the experimental group) and 28 males from a community who did not participate in the HES (the control group). In this study, the personal interview and review of relevant documents were the methods used in the collection of data. Descriptive and inferential statistics were employed in the data analysis. The findings showed that the HES was effective in imparting NFP knowledge and in raising the awareness of the participants on their family planning responsibilities, but was only partially successful in developing the desired behavior and practices. This study also highlighted the limitations of the different program components of the HES that affected its outcomes. These include the absence of specific indicators in its objectives, the limited resources used in program implementation, short program duration and the restricted scope of the topics that were covered.